Effects of melatonin on the nitric oxide system and protein nitration in the hypobaric hypoxic rat hippocampus. Issue 1 (December 2015) - Huang, Chih-Chia; Lai, Chia-Jou; Tsai, Mang-Hung; Wu, Ya-Chieh; Chen, Kuang-Ti; Jou, Ming-Jia; Fu, Pin-I; Wu, Ching-Hsiang; Wei, I-Hua
Abstract Background It is well documented that the nitric oxide (NO) might be directly involved in brain response to hypobaric hypoxia, and could contribute to memory deficiencies. Recent studies have shown that melatonin could attenuate hypoxia or ischemia-induced nerve injuries by decreasing the production of free radicals. The present study, using immunohistochemical and immunoblot methods, aimed to explore whether melatonin treatment may affect the expression of nitric oxide system and protein nitration, and provide neuroprotection in the rat hippocampus injured by hypobaric hypoxia. Prior to hypoxic treatment, adult rats were pretreated with melatonin (100 mg/kg, i.p.) before they were exposed to the altitude chamber with 48 Torr of the partial oxygen concentration (pO2 ) for 7 h to mimic the ambience of being at 9000 m in height. They were then sacrificed after 0 h, 1, and 3 days of reoxygenation. Results The results obtained from the immunohistochemical and immunoblotting analyses showed that the expressions of neuronal nitric oxide synthase (nNOS), endothelial nitric oxide synthase (eNOS), inducible nitric oxide synthase (iNOS), nitrotyrosine (Ntyr) and Caspase 3 in the hypoxic hippocampus were increased from 0 h to 3 days of reoxygenation. Interestingly, the hypoxia-induced increase of nNOS, eNOS, iNOS, Ntyr and Caspase 3 protein expression was significantly depressed in the hypoxic rats treated with melatonin. Conclusions Activation of the nitric oxide system and protein nitration constitutes a hippocampal response to hypobaric hypoxia and administration of melatonin could provide new therapeutic avenues to prevent and/or treat the symptoms produced by hypobaric hypoxia.